О находке моллюска Mya arenaria L. (Bivalvia) в северо-западной части Черного моря - Бешевли, Л.Е.; Колягин, В.А. (Вестник зоологии, 1967)
On the 20th of November and 18th of Desember, 1966 in the region of Odessa 2 alive specimens of the Mya arenaria L. mollusk, new for the Black Sea, and some shells of the same species were found on the beach. Individual variability of the M. arenaria shell form is shown in the fig. 2. The size of the mollusks which were found in the Black Sea varies in the range of 35— 60 mm.
As in our collection there are individuals and valves of the various size, one may suppose that M. arenaria inhabits the Black Sea already for some years.
The appearance of this arcticboreal species reaffirms the expediency of the sugges-tions made by V. A. Vodyanitsky and T. S. Rass (1958, 1961, 1965) and by K. A. Vinogra-dov (1947, 1949) concerning the implantation of the north-atlantic fauna representatives of the industrial value into the Black Sea.